2012
DOI: 10.1063/1.3693307
|View full text |Cite
|
Sign up to set email alerts
|

Strain effect analysis on the thermoelectric figure of merit in n-type Si/Ge nanocomposites

Abstract: In this paper, the effect of strain on the thermoelectric figure of merit is investigated in n-type Ge nanowire-Si host nanocomposite materials. The Seebeck coefficient and electrical conductivity of the Si–Ge nanocomposites are calculated using an analytical model derived from the Boltzmann transport equation (BTE) under the relaxation-time approximation. The effect of strain is incorporated into the BTE through the strain induced energy shift and effective mass variation calculated from the deformation poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the other hand, Xu and Li investigated the effect of the strain types on the thermoelectric properties of Si-Ge nanocomposites based on the deformation potential theory and a degenerate kÁp method. 23 This study showed that the room-temperature ZT decreases by as large as 40% under 1% of shear or biaxial strain, whereas it exhibits around 10% increase when orthorhombically strained, but the origin of the difference was not identified.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…On the other hand, Xu and Li investigated the effect of the strain types on the thermoelectric properties of Si-Ge nanocomposites based on the deformation potential theory and a degenerate kÁp method. 23 This study showed that the room-temperature ZT decreases by as large as 40% under 1% of shear or biaxial strain, whereas it exhibits around 10% increase when orthorhombically strained, but the origin of the difference was not identified.…”
Section: Introductionmentioning
confidence: 80%
“…However, Xu and Li demonstrated that k l under external strain deviates from the unstrained value only by 2% or less, and that the deviation is smaller for S o than S b or S s . 23 Based on this observation, k l is approximated as the unstrained value (0.63 W m À1 K À1 (ref. 10)), and the results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical study of such an approach was performed for Si/Ge composites in which an ordered array of nanoscale Si wires was embedded into a Ge matrix, and it was found to be rather promising. 185,186 Some of the other parameters mentioned above, in particular electric and magnetic fields, have rarely been considered, even in ambient-pressure studies of thermoelectric materials. However, both of these parameters have great potential to enhance the Seebeck coefficient, via the two-dimensional electron gas induced by an applied electric field [187][188][189] or via the strong magnetothermoelectric effects induced by an applied magnetic field.…”
Section: Future Perspectives and Strategiesmentioning
confidence: 99%
“…Other methodologies to engineer the band structure or scattering mechanism in NCs that do not require rigorous periodic geometric structures are also proposed. For example, Xu and Li [ 193 ] used the deformation potential theory and a degenerate k·p method to investigate the strain effect of n -type Si/Ge NCs which could induce energy band shift and effective mass variation. Popescu and Woods [ 194 ] investigated electronic structure modified by the locally distorted DOS induced by spherical nanoinclusions embedded in bulk PbTe.…”
Section: Modeling Of Electrical Carrier Transportmentioning
confidence: 99%